A Systematic Review: The Use of Pictures in Teaching Simple Present Tense Sentence Construction to Junior High School Students - Agustinus Nai Aki; Olga A. Rorintulus (Journal of English Language Teaching, Literature and Culture, 2023)
The research aims to show the use of pictures to teach simple present tense sentence construction to English young learners. It is important to teach sentence construction to young learners because young learners must begin to make their selves familiar with constructing sentences before they develop and improve their English to the next levels. The method used in conducting this research was Systematic Review to determine the use of pictures in teaching simple sentence construction to English young learners. There were 10 articles from year 2010 – 2022 related to the titles analyzed by the researcher by using Systematic Review. As the result of the research, it is concluded that teaching English using pictures enable young learners to construct simple sentences in English.